Glycerol Derivatives of Fatty Acid and Other Constituents from Straw of Oryza sativa - Chung, Ill-Min; Yu, Bo-Ra; Kim, Seung-Hyun; Ahmad, Ateeque (Asian Journal of Chemistry, 2014)
Four compounds glyceryl-dioleo-linoleate (1), n-heptadecanyl oleate (2), n-tridecanyl n-octadec-9,12-dienoate (3), n-hexacos-14-enoic acid (4) were isolated from the methanol extract of Oryza sativa of rice straw. The structures have been elucidated with the help 600 MHz NMR using 1D spectral methods viz., 1H and 13C, aided by ESI/FTMS and IR spectroscopy. The compounds 1-4 are reported for the first time in rice straw of O. sativa.